2009
DOI: 10.1560/ijps.57.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Pollen sources for honeybees in Israel: Source, periods of shortage, and influence on population growth

Abstract: The nutritional demands of honeybees are met by two plant-produced components: nectar and pollen, the contents of which vary among floral sources. In Israel, there is an extraordinary richness in plant species, and one of the dominant insect pollinators is the honeybee (Apis mellifera L.). July to February is characterized as a period of low flower abundance for local species in general and for bee forage plants in particular. In this study, we monitored the amount and number of pollen sources collected by hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 20 publications
4
24
0
1
Order By: Relevance
“…In a diverse habitat, colonies tend to collect pollen from a variety of sources (24). But in disturbed habitats and extensive agricultural monocultures, the breadth of the diet is reduced (25), and bees may suffer from a deficiency of eFAs.…”
mentioning
confidence: 99%
“…In a diverse habitat, colonies tend to collect pollen from a variety of sources (24). But in disturbed habitats and extensive agricultural monocultures, the breadth of the diet is reduced (25), and bees may suffer from a deficiency of eFAs.…”
mentioning
confidence: 99%
“…Diversity in bee diets may be necessary to avoid nutritional deficiencies (Schmidt et al 1995) and to dilute toxins, but need not involve many plant species. Honeybee colonies sampled at various sites in Israel over a year usually collected pollen from 5-9 species at a time (Avni et al 2009). Similar dependence on a few pollen sources was noted by Keller et al (2005), based mainly on Swiss studies, and mixed pollens from five plant species were found to be better than single pollens for maintaining honeybee immune systems (Alaux et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…To define low, moderate and high quality habitats, this categorical descriptor incorporated information on the availability of non-crop foraging habitat, nesting habitat and the intensity of agricultural land use. In the case of the honeybees, high quality habitats could have provided a greater availability of foraging resources in periods preceding peak oilseed rape flowering, which may have led to increased colony provisioning and so colony growth (Avni et al, 2009). Greater numbers of workers per colony would have had a knock on impact on visitation rates.…”
Section: Within-field and Landscape Scale Spatial Effectsmentioning
confidence: 99%